Pemanfaatan Aplikasi Quizizz sebagai Media Evaluasi Interaktif dalam Proses Belajar Mengajar Bahasa Jerman - Apituley, Patresia Silvana; Lestuny, Carolina (Gaba-Gaba : Jurnal Pengabdian Kepada Masyarakat dalam Bidang Pendidikan Bahasa dan Seni, 2024)
This activity was organized as an effort to assist German language teachers in getting to know and utilizing Quizizz, an online-based evaluation application designed to create a more interactive, fun, and meaningful learning atmosphere. In the midst of technological developments and the demands of the Merdeka Curriculum, which emphasize learner-centered learning and the use of digital media, teachers are required to be more adaptive in choosing and developing evaluation tools that suit the needs of the times. Quizizz offers an alternative that not only facilitates real-time evaluations but also provides direct feedback to students and allows for the integration of game elements that can enhance learning motivation. This training is carried out face-to-face through a workshop approach and hands-on practice, so that participants not only understand the theory, but also have the opportunity to try directly and develop contextualized evaluation questions for German language learning. German language learning. Based on the results of the training, the participants showed an increase in their understanding of the use of technology in learning, especially in developing more creative and interesting evaluations. In addition, teachers also said that the use of Quizizz had a positive impact on student participation, because the evaluation atmosphere became more relaxed but still meaningful. Thus, this activity not only strengthens teachers' capacity in terms of technology utilization but also encourages the creation of an evaluation process that is more humancentered and relevant to the characteristics of 21st-century learning.